Analysis of Parking Needs and System in Bengkayang Central Market - Arfando, Gio; Azwansyah, Heri; Mukti, Elsa Tri (Fakultas Teknik Universitas Tanjungpura, 2025)
Bengkayang Regency, located in West Kalimantan Province, plays a strategic role as an economic and trade centre in the border region. One of its busiest areas is the Bengkayang Central Market, a hub for the distribution of goods and services. The high intensity of trading activities has led to increased parking demand, which, if left unmanaged, can result in congestion, reduced comfort, and disruptions to traffic flow. This study aims to identify parking characteristics, determine parking space requirements, and propose alternative arrangements for the Bengkayang Central Market. Primary data were collected through direct observations of parking inventory and vehicle entry